GENE EXPRESSION IN ESCHERICHIA COLI DURING PROLONGED-INCUBATION - Patel, Bansri (My University, 2018)
Environments, where growth is limited by the availability of nutrients are common, for example, soil, water, or even host environments such as macrophages, can lack essential nutrients to support growth. As such, many bacteria spend most of their time in states of little or no growth due to starvation. The starved and growth attenuated state is now widely considered as an important physiological condition in bacterial pathogenesis and survival. Experiments studying stationary phase and adaptation mechanisms to non-optimal conditions lead to the discovery of RpoS as a growth phase-dependent sigma factor. Though RpoS controls many genes in the early stationary phase, it is not known whether RpoS is necessary for prolonged slow growth or not. In a previous study to identify genes controlled by RpoS, we found that a large fraction of the E. coli genome continues to increase in expression during prolonged starvation that does not require RpoS. This suggests that other growth-phase-dependent regulatory mechanism, in addition, to RpoS, may control prolonged stationary phase gene expression. In this study, we examined the abundance of transcripts to identify and characterize the genes that are preferentially expressed during prolonged-incubation phase. RpoS independent genes that are expressed in higher abundance during prolonged-incubation include iron acquisition genes, enterobactin biosynthesis, arginine degradation, and 2-methycitrate pathways enzyme coding-genes. Putative fimbriae genes associated with adhesion to biotic and abiotic surfaces are expressed as RpoS-dependent genes. Furthermore, several biofilm formation genes are expressed in planktonic cultures. Altogether, other regulators, in addition to RpoS, regulate the gene expression during the prolonged-incubation phase and the genes are likely to be important for survival during the prolonged-incubation phase.